2009
DOI: 10.1117/12.817170
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical evaluation of a variable friction tactile interface

Abstract: This study explores the haptic rendering capabilities of a variable friction tactile interface through psychophysical experiments. In order to obtain a deeper understanding of the sensory resolution associated with the Tactile Pattern Display (TPaD), friction discrimination experiments are conducted. During the experiments, subjects are asked to explore the glass surface of the TPaD using their bare index fingers, to feel the friction on the surface, and to compare the slipperiness of two stimuli, displayed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
(9 reference statements)
2
14
0
Order By: Relevance
“…Furthermore, the Weber fraction of the perceived weight of a grasped object is around 10 percent [2], which is also similar to our value, although Giachritsis et al reported a slightly lower value of 6 percent [3]. As to the one-fingered and active touch condition, the Weber fraction of the friction coefficients of smooth surfaces was reported to be 18 percent across wide range of friction coefficients (0.2-1.0) [32]. This and our values are reasonably close despite the difference of active and passive touch.…”
Section: Review Of Dls In Related Studiessupporting
confidence: 92%
“…Furthermore, the Weber fraction of the perceived weight of a grasped object is around 10 percent [2], which is also similar to our value, although Giachritsis et al reported a slightly lower value of 6 percent [3]. As to the one-fingered and active touch condition, the Weber fraction of the friction coefficients of smooth surfaces was reported to be 18 percent across wide range of friction coefficients (0.2-1.0) [32]. This and our values are reasonably close despite the difference of active and passive touch.…”
Section: Review Of Dls In Related Studiessupporting
confidence: 92%
“…Considering that the base friction was approximately 0.2 N as shown in Fig. 5(a), the just noticeable difference (JND) in this measurement was approximately 20%, which coincides with a study reporting that the JND of friction is 18% [29]. The results show that the device can provide wide range of perceptible haptic feedback from, at least, 0.04 N to beyond 1 N.…”
Section: Threshold Of Haptic Feedbacksupporting
confidence: 82%
“…Hence, in order to modulate friction on a touch surface properly, it is important to understand our tactile perception of change in friction and the contact mechanics behind it. Although, the earlier studies have investigated the contact mechanics of friction [5], [10]- [17] and our perceptual ability to discriminate two different surfaces based on friction [18]- [20], the number of studies investigating the intermittent contact mechanics during a change in friction on a touch surface is very limited [21]- [24]. Furthermore, the factors affecting our tactile perception of this change have not been investigated in depth yet [22]- [26].…”
Section: Introductionmentioning
confidence: 99%